UPAYA DINAS KEBUDAYAAN DAN PARIWISATA DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN (Studi Pada Dinas Kebudayaan, Pariwisata, Pemuda Dan Olahraga Kabupaten Sumenep) - Fitriyah Ema Ningsih; Rizki Yudhi Dewantara (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
Sumenep is one of the districts on Madura Island, East Java which located on the tip of Madura Island. The diversity of tourism potential is supported by tourism development which aims to increase the amount of tourist visits to Sumenep through a Visit Sumenep 2018 program or the year of tourist visits. Therefore, in carrying out the tourism development in the tourist area the support and efforts made by the government to support the success of tourism development through the Department of Culture and Tourism of Sumenep are needed, so the researcher raised the title